2018
DOI: 10.21037/atm.2018.09.33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erlotinib plus bevacizumab on brain metastases in patients with non-small cell lung cancer

Abstract: Background: The standard therapy for brain metastasis (BM) in non-small cell lung cancer (NSCLC) is radiation therapy (RT), although it is associated with complications such as leukoencephalopathy. In the current report, we retrospectively review data from eight patients who had NSCLC and harbored epidermal growth factor receptor (EGFR) mutations, and who were received erlotinib plus bevacizumab (E+B) as firstline therapy for BM.Methods: Patients were given E+B as first therapy for BM until August 2017 at our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
1
13
1
Order By: Relevance
“…Combination treatment with EGFR-TKIs and antiangiogenic agents has shown a greater e cacy compared with EGFR-TKI monotherapy in patients with EGFR-mutated NSCLC [13,14,20]. The combination of EGFR-TKIs with bevacizumab has also shown encouraging results in EGFR mutation-positive NSCLC patients with brain metastases [30,31]. On the other hand, patients with brain metastases treated with antiangiogenic agents have been thought to be more susceptible to CNS hemorrhage at sites of intracranial lesions because of the occurrence of a fatal cerebral hemorrhage in a phase 1 study [32].…”
Section: Discussionmentioning
confidence: 99%
“…Combination treatment with EGFR-TKIs and antiangiogenic agents has shown a greater e cacy compared with EGFR-TKI monotherapy in patients with EGFR-mutated NSCLC [13,14,20]. The combination of EGFR-TKIs with bevacizumab has also shown encouraging results in EGFR mutation-positive NSCLC patients with brain metastases [30,31]. On the other hand, patients with brain metastases treated with antiangiogenic agents have been thought to be more susceptible to CNS hemorrhage at sites of intracranial lesions because of the occurrence of a fatal cerebral hemorrhage in a phase 1 study [32].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor produced in the perinecrotic area is thought to be a major cause of both angiogenesis and perilesional edema after radiation therapy to metastatic lesions of the brain [9]. The efficacy and safety of bevacizumab treatment for brain metastasis of NSCLC are well known [10-12], while efficacy of bevacizumab combined with EGFR-TKIs for EGFR -mutated NSCLC with brain metastasis has also been reported [13, 14]. Furthermore, Mairinger et al [15] reported that angiogenesis was also activated to some extent in LCNECs.…”
Section: Discussionmentioning
confidence: 99%
“…122 In addition, there are reports recommending the use of bevacizumab in combination with erlotinib as a rst-line treatment for brain metastases. 123…”
Section: Erlotinibmentioning
confidence: 99%